Association of Caribbean States : promoting the sustainable development of the greater Caribbean (FIRST LondonGB, 2011)
Includes country profiles. Focuses on regional integration, foreign relations, disasters, sustainable development, trade development, governance of the Caribbean Sea.
Keywords: REGIONAL INTEGRATION